Finite Element Reconstruction of a Mandibular First Molar - Ehsani, Sara; Mirhashemi, Fatemeh Sadat; Asgary, Saeed (Iranian Endodontic Journal, 2013)
Introduction: Mandibular first molar is the most important tooth with complicated morphology. In finite element (FE) studies, investigators usually prefer to model anterior teeth with a simple and single straight root; it makes the results deviate from the actual case. The most complicated and time-consuming step in FE studies is modeling of the desired tooth, thus this study was performed to establish a finite element method (FEM) of reconstructing a mandibular first molar with the greatest precision. Materials and Methods: An extracted mandibular first molar was digitized, and then radiographed from different aspects to achieve its outer and inner morphology. The solid model of tooth and root canals were constructed according to this data as well as the anatomy of mandibular first molar described in the literature. Result: A three-dimensional model of mandibular first molar was created, giving special consideration to shape and root canal system dimensions. Conclusion: This model may constitute a basis for investigating the effect of different clinical situations on mandibular first molars in vitro, especially on its root canal system. The method described here seems feasible and reasonably precise foundation for investigations.